PROFILE OF THE PATIENTS TREATED IN A COMPREHENSIVE WOUND CARE UNIT - Ruiz, Paula Buck de Oliveira; Poletti, Nadia Antonia Aparecida; Lima, Antônio Fernandes Costa (Cogitare Enfermagem, 2022)
Objective: to analyze the demographic, clinical and therapeutic profiles of the patients treated in a Comprehensive Wound Care Unit. Method: a quantitative and retrospective study that analyzed management reports and medical records of patients with chronic wounds treated at a Comprehensive Wound Care Unit in Vitória da Conquista-Bahia, Brazil. The data, collected in February 2020, were submitted to descriptive and inferential analysis, and the Chi-square test with p-value<0.05 was used for the association between variables. Results: the mean age among the 176 patients was 71.4 years old (SD±16.5). There was a statistical association between fecal incontinence and stage two Pressure Injury (p=0.018); Diabetes Mellitus and stage three Pressure Injury (p<0.001); Alzheimer’s disease and medical device-related injury (p=0.028); Diabetes Mellitus and Diabetic Ulcer (p<0.001); and between vascular insufficiency and Venous Ulcer (p<0.001). Conclusion: knowledge about the profiles provides the basis for the comprehensive assistance provided by a non-hospital unit specialized in wounds.